Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1210/jc.2013-3394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Lifestyle Program on Vascular Reactivity in Macro- and Microcirculation in Severely Obese Adolescents

Abstract: Macro- and microvascular endothelial function are preserved in adolescents with severe obesity. Conversely, weight loss does not improve their impaired smooth muscle response to exogenous organic nitrate in both vascular beds, despite reducing plasma markers adversely related to vascular homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
3
15
1
Order By: Relevance
“…In our study, the population of patients with obesity displayed a slight impaired endothelium‐dependent vasodilatation compared with our previous report . However, the mild endothelial dysfunction found in our population of patients with obesity could be explained by the fact that the population of women was young (mean, 21 years), as Montero et al reported an absence of endothelium‐dependent vasorelaxation in young participants with obesity .…”
Section: Discussioncontrasting
confidence: 61%
“…In our study, the population of patients with obesity displayed a slight impaired endothelium‐dependent vasodilatation compared with our previous report . However, the mild endothelial dysfunction found in our population of patients with obesity could be explained by the fact that the population of women was young (mean, 21 years), as Montero et al reported an absence of endothelium‐dependent vasorelaxation in young participants with obesity .…”
Section: Discussioncontrasting
confidence: 61%
“…Although Endo-PAT was initially set forth as an alternative technique for FMD, a large population-based study recently pointed out that micro-(measured with Endo-PAT) and macrovascular (detected with FMD) endothelial dysfunctions can develop independently of each other (66). Microvascular endothelial dysfunction would precede endothelial dysfunction at the macrovascular level in obese children (12). To conclude, …”
Section: Technological Advancements In Obesity-associated Endothelialmentioning
confidence: 98%
“…Endothelial micro particles (EMP) (12,13) as well as endothelial progenitor cells (EPC) (14) and circulating angiogenic cells (CAC) (15) emerged as markers of respectively endothelial damage and repair. All have been implicated in the process of childhood obesity-related endothelial dysfunction (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, whether lifestyle interventions are also capable of reversing endothelial dysfunction at the microvascular level is currently not clear. 9 In recent decades, novel insights have been obtained into the mechanistic basis for endothelial homeostasis. First, endothelial progenitor cells (EPCs) were recognized as important contributors of endothelial repair 10 because they are able to replace lost endothelial cells.…”
Section: What This Study Addsmentioning
confidence: 99%